Aplikasi Praktis Biomekanika dalam Pendidikan Jasmani dan Olahraga - Soeharsono Soeharsono (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2005)
Biomechanics of Sport learns the performances in sport skills. Result expected is the acquisition of knowledge and ability to analyze some sport techniques whichare safe, efficient, and effective; being capable to detect the wrong or correct techniquesand also being able to remedy it precisely. Besides, it is also expected that certaincapacities of doing renovation can be afforded. It is much better if there are some capabilities to provide or create some appropriate new methods.Out of the sport techniques, there are also needed some supporting factors such as:mechanical principles, balance, move patterns consisted of linear, rotation, and complex moves, moving area, that are of planar and non-planar area, cardinal area consisted of sagital, frontal and transversal area. Also about kinetics that is the cause ofmovement, and kinematics that is the study of object movement with time and spatialconcept regardless of its causes.Moreover, teachers of physical education require to have a minimal base of biomechanics of sport, though is not circumstantial but extent. Meanwhile, coaches require tomastering its basic and also broad knowledge, so that they are able to improve untilthe highest technique.Keyword: Application, Biomechanics